Time and temperature dependent mechanical behavior of HFPE-II-52 polyimide at high temperature. (September 2016) - Xu, Yi; Bhargava, Peeyush; Zehnder, Alan
Highlights: HFPE-II-52 undergoes extensive creep and relaxation at high temperatures and stresses. Linear viscoelasticity + state variable viscoplasticity models the mechanical response. The model is used in Abaqus to model shear yield in a polyimide matrix composite. Abstract: Motivated by demanding, high temperature applications of polyimides and polyimide matrix composites, this study characterizes the high temperature, time and temperature dependent mechanical behavior of HFPE-II-52 polyimide. Three types of experiments: creep recovery, multistep relaxation and fixed strain rate tension tests were performed at temperatures from 285 °C to 315 °C. A constitutive model combining linear viscoelasticity with viscoplasticity was developed. The viscoplastic part of the model uses a power law flow potential with state variable evolution to model strain hardening and softening. The full model was fit to the experimental data and is shown to capture the key features of the material behavior. The constitutive model was also generalized to 3D and implemented as an ABAQUS user material. Plane-stress finite element simulations of a high temperature tension test and 3D simulations of a unidirectional laminate under axial shear loading were performed as example applications of the model. Graphical abstract: